2023
DOI: 10.22178/pos.89-8
|View full text |Cite
|
Sign up to set email alerts
|

Measures by Organisations to Counter Challenges in the Use of Information Technology in Protecting Personal and Business Data in Nairobi County, Kenya

Abstract: Globally, most states have adopted new technologies that have seen many process improvements and cost optimisations and enabled them to provide value-added services to their citizens, thereby improving quality of life and achieving rapid growth and development in various sectors of the nation. Kenya is one of the developing countries that has benefited from adopting modern ICT in recent years. Despite government efforts to ensure the successful integration of ICT into various state departments and the private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Regression model outcomes revealed that coffee societies in Nyeri county Kenya had not fully implemented the computerized accounting systems. The cost, human resource expertise, and availability of associated infrastructures were the greatest significant constrains hindering the implementation of the system; and workers' perception on the systems were insignificant in respect to the acceptance of systems Kimani (2016) conducted an investigation to explore the influence of information technology on the operational effectiveness of Population Services, Kenya. In this study, primary data was gathered through a semi-structured questionnaire.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Regression model outcomes revealed that coffee societies in Nyeri county Kenya had not fully implemented the computerized accounting systems. The cost, human resource expertise, and availability of associated infrastructures were the greatest significant constrains hindering the implementation of the system; and workers' perception on the systems were insignificant in respect to the acceptance of systems Kimani (2016) conducted an investigation to explore the influence of information technology on the operational effectiveness of Population Services, Kenya. In this study, primary data was gathered through a semi-structured questionnaire.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…This gap was taken care of in this study by the use of a mixed methods approach. Further, obtainable studies regarding the effect of record retention on firm performance (Matto (2022); Gitau Kimani (2023); Adom-Nyankey and Andoh (2022); Ndenge (2022)) were carried out in different geographical location hence their findings could not be used to explain the situation in Lira City in regards to the contribution of record filling on organisational performance. Also, a study by Matto (2022) only used quantitative approach.…”
Section: Record Retrieval and Performance Of The Firmmentioning
confidence: 99%
“…When a thing is not recognisable 15 14 Shared items/documents with colleagues not well documented 15 14…”
Section: Causementioning
confidence: 99%
“…The author [15] identified the struggle of most agencies that deal with enormous amounts of data, such as Kenya Data Network (KDN) and Kenya Revenue Authority (KRA), due to failed database systems. In addition, more complaints have been recorded by the public day in and day out that documents are lost without a trace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation